Effects of Self-Regulation vs. External Regulation on the Factors and Symptoms of Academic Stress in Undergraduate Students - de la Fuente, Jesús; Peralta-Sánchez, Francisco Javier; Martínez-Vicente, Jose Manuel; Sander, Paul; Garzón-Umerenkova, Angélica; Zapata, Lucía (Frontiers in Psychology, 2020)
The SRL vs. ERL theory has shown that the combination of levels of student self-regulation and regulation from the teaching context produces linear effects on achievement emotions and coping strategies. However, a similar effect on stress factors and symptoms of university students has not yet been demonstrated. The aim of this study was to test this prediction. It was hypothesized that the level of student self-regulation (low/medium/high), in interaction with the level of external regulation from teaching (low/medium/high), would also produce a linear effect on stress factors and symptoms of university students. A total of 527 undergraduate students completed validated questionnaires about self-regulation, regulatory teaching, stress factors and symptoms. Using an ex post facto design by selection, ANOVAs and MANOVAs (3 x 3; 5 x 1; 5 x 2) were carried out. The results confirmed that the level of self-regulation and the level of regulatory teaching jointly determined the level of stress factors and symptoms of university students. Once again, a five-level heuristic of possible combinations was configured to jointly determined university students’ level of academic stress. We concluded that the combination of different levels of student regulation levels and regulation from teaching process jointly determines university students’ level of academic stress. The implications for university students’ emotional health, stress prevention and well-being are established.